LEGAL CITIZENSHIP: JUDICIAL ACTIVISM AND JUDICIALIZATION OF POLITICS IN BRAZIL - Barbosa, Agnaldo de Sousa [UNESP]; Morais Colombaroli, Ana Carolina de (Univ Fed Pernambuco, 2016)
This paper aims to analyze the processes of judicial activism, judicialization of the politics and of the sociability in the Brazilian scene. It intends to discuss the democracy building in the country after the Federal Constitution of 1988, emphasizing the importance of the access to the justice for the construction of a permanent political activity. It questions the capability of law as an instrument for empowerment, assuming that it should be understood beyond the norm The discussion about the thejudicialization and judicial activism is done, mainly, from the perspective of the social sciences, presenting the reasons for the judicialization, how it occurred, its consequences, and the main differences between the judicialization and the judicial activism. Finally, it talks about the procedural revolution due to the 1988 Constitution, highlighting the issues of access to justice and protection of collective rights.
Keywords: Judicialization of the politics; Judicial activism; Democratic building; Emancipation